A comparison of three scales for measuring pain in children with cognitive impairment. (15th August 2014) - Massaro, Marta; Ronfani, Luca; Ferrara, Giovanna; Badina, Laura; Giorgi, Rita; D'Osualdo, Flavio; Taddio, Andrea; Barbi, Egidio
Abstract Aim Pain is a neglected problem in children with cognitive impairments, and few studies compare the clinical use of specific pain scales. We compared the Non‐Communicating Children's Pain Checklist Postoperative Version (NCCPC‐PV), the Echelle Douleur Enfant San Salvador (DESS) and the Children's Hospital of Eastern Ontario Pain Scale (CHEOPS). The first two were developed for children with cognitive impairment, and the third is a more general pain scale. Methods Two external observers and the child's caregiver assessed 40 children with cognitive impairment for pain levels. We assessed inter‐rater agreement, correlation, dependence on knowledge of the child's behaviour, simplicity and adequacy in pain rating according to the caregiver for all three scales. Results The correlation between the NCCPC‐PV and the DESS was strong (Spearman correlation coefficient = 0.76) and better than between each scale and the CHEOPS. Although the DESS showed better inter‐rater agreement, it was more dependent on familiarity with the child and was judged more difficult to use by all observers. The NCCPC‐PV was the easiest use and the most appropriate for rating the child's pain. Conclusion The NCCPC‐PV was the easiest to use for pain assessment in cognitively impaired children and should be adopted in clinical settings.